In Search of Real Circumcision Ritual Failure and Circumcision in Paul - Smit, Peter-Ben 1979- (2017)
This article applies the theoretical framework of ritual failure', a sub-discipline of ritual criticism, to Paul's discussion of circumcision in his letter to the Galatians, Philippians and Romans. It is argued that the application of this theoretical perspective clari?es the dynamics at stake and provides a new way of understanding the development in Paul's position regarding circumcision. There is movement from an attitude of strong propagation, by way of indifference and a subsequent attitude of rejection, to one of modified reintegration into Paul's thinking. At every turn of this development, ritual failure plays a pivotal role and functions as a catalyst for the development of Paul's theology.
Keywords: Bible. Galatians; Bible. Romans; Circumcision -- Religious aspects; Galatians; Paul; Philippians; RITES & ceremonies; Romans; Theology; Circumcision; ritual criticism